An Interdisciplinary Role of Artificial Intelligence (AI) in Dentistry: A Focus on Endodontics, Oral Pathology, Prosthodontics, Orthodontics, and Periodontics - Shweta Vijaykumar Sagare; Pratiksha Kumar; Rashmita Nayak; Ashtha Arya; Akshata Patil; Maninderjit Kaur; Geetpriya Kaur (Journal of Pharmacy and Bioallied Sciences)
Background: Artificial intelligence (AI) has emerged as a transformative tool in modern dentistry, enhancing diagnosis, treatment planning, and patient outcomes. Materials and Methods: This study explores AI applications across five dental specialties—endodontics, oral pathology, prosthodontics, orthodontics, and periodontics—using a structured questionnaire distributed to 500 dental professionals. Results: Results were synthesized into statistical analyses to assess AI’s impact on clinical efficiency, diagnostic accuracy, and patient satisfaction. Conclusion: The study concludes with insights into AI’s interdisciplinary role in dentistry and potential future advancements.